THE INFLUENCE OF ELECTRONIC WORD OF MOUTH AND HALAL LABELING ON THE PURCHASE INTENTION OF SOMETHINC SKINCARE WITH BRAND IMAGE AS A MEDIATING VARIABLE IN UNIVERSITAS SYIAH KUALA STUDENTS - Husna, Nurul; Kesuma, T.Meldi (International Journal of Kita Kreatif, 2024)
This research aims to analyze the influence of electronic word of mouth and halal labeling on interest in purchasing certain types of skincare with brand image as a mediating variable. The objects of this research are students at Syiah Kuala University. This research uses a quantitative approach, with a probability sampling method using proportional random sampling technique with a sample size of 100 respondents. The data analysis techniques used are path analysis and Sobel test. Based on the results of the research analysis, it was found that electronic word of mouth had a positive and significant effect on buying interest. Halal labeling has a positive and significant effect on purchasing interest. Electronic word of mouth has a positive and significant effect on brand image. Halal labeling has a positive and significant effect on brand image. Brand image has a positive and significant effect on purchasing interest. And the results of the Sobel test on indirect influence show that brand image mediates the influence of electronic word of mouth and halal labeling on purchasing interest.Keywords: Electronic Word Of Mouth, Halal Labeling, Purchase Intention, Brand Image, Skincare Somethinc